On harmonic curvatures of a Frenet curve in Lorentzian space - Kulahci, Mihriban; Bektas, Mehmet; Erguet, Mahmut (Pergamon-Elsevier Science Ltd, 2009)
In this paper, we consider curves of AW(k)-type, 1 <= k <= 3, in Lorentzian space. We give curvature conditions of these kind of curves. Furthermore, we study harmonic curvatures of curves of AW(k)-type. We investigate that under what conditions AW(k)-type curves are helix. Some related theorems and corollaries are also proved. (C) 2008 Elsevier Ltd. All rights reserved.